"Ordinary people only": knowledge, representativeness and the publics of public participation in healthcare - Martin, Graham P. (Blackwell Publishing, 2008)
Public involvement in healthcare is a prominent policy in countries across the economically developed world. A growing body of academic literature has focused on public participation, often presenting dichotomies between good and bad practice: between initiatives that offer empowerment and those constrained by consumerism, or between those which rely for recruitment on self-selecting members of the public, and those including a more broad-based, statistically representative group. In this paper I discuss the apparent tensions between differing rationales for participation, relating recent discussions about the nature of representation in public involvement to parallel writings about the contribution of laypeople’s expertise and experience. In the academic literature, there is, I suggest, a thin line between democratic justifications for involvement, suggesting a representative role for involved publics, and technocratic ideas about the potential ‘expert’ contributions of particular subgroups of the public. Analysing recent policy documents on participation in healthcare in England, I seek moreover to show how contemporary policy transcends both categories, demanding complex roles of involved publics which invoke various qualities seen as important in governing the interface between state and society. I relate this to social-theoretical perspectives on the relationship between governmental authority and citizens in late-modern society.